Pengaruh Kepemimpinan, Kompensasi, dan Lingkungan Kerja terhadap Kinerja Karyawan Bagian Produksi PT Ramajaya Pramukti Kecamatan Tapung Kabupaten Kampar - Fika Rama Lestari; Marzolina Marzolina; Henni Noviasari (Program Studi Manajemen FEBM UMRAH, 2023)
This study aims to determine the effect of Leadership (X1), Compensation (X2),, and Work Environment (X3), on the Performance (Y) of Employees of the Production Division of PT. Ramajaya Pramukti, Tapung District, Kampar Regency. The research population was 163 people and for sampling using the slovin method were 116 people. The data analysis method used multiple linear regression analysis with the help of SPSS software. The results show that: 1) Leadership has a significant effect on performance; 2) Compensation has a significant effect on performance; 3) Work environment has a significant effect on performance; 4) Leadership, Compensation, and Work Environment have a significant effect on performance.